Premarital Sex among Adolescent Street Children in Pekanbaru - Yessi Harnani; Agus Alamsyah; Al Hidayati (International Journal of Public Health Science (IJPHS), 2018)
Premarital sex is any behavior that is driven by sexual desire with the opposite sex before marriage. Some premarital sex activities include feeling, kissing, necking, petting, and intercourse. Premarital sex in adolescents has a negative impact such as unwanted pregnancy, unsafe abortion, resulting in increased maternal, neonatal deaths and perinatal, increasing the incidence of HIV / AIDS, dropping out of school. To Know Relations factors knowledge, girlfriend status, exposure to pornography, family harmony, the negative influence of peers and parental supervision with premarital sex on street adolescent girls. Quantitative analytical observational method with cross sectional design. Samples of 100 teenage children street children in Pekanbaru City. Snow ball sampling technique, Instrument is a questionnaire. Univariate data analysis, multivariate bivariate with logistic regression test. showed 65% (65 people) prenup sex, 78% dating, 74% pornography exposure, peer influence 70%, lack of knowledge of youth 61%, family not harmonious 80%, and low parental supervision 57 %. The related variables (p value <0.05) with premarital sex behavior are boyfriend status, pornographic exposure and peer influence. Status girlfriend most risky 39 times premarital sex. There is relationship and influence of 3 factors to premarital sex on adolescent child of Street of Pekanbaru Town. Suggestions for the formation of containers such as peer counselor and BKR (Youth Family Development) as a precautionary measure to increase the number of premarital sex incidents in the juveniles Street Children Pekanbaru.